(untitled) (Teología, 2022)
The relations that Kusch established with the Argentine current of liberation philosophy and the encounter with the Argentine current of liberation theology. In these encounters and intersections, Rodolfo Kusch’s thinking on native religions, popular thought, religiosity and popular wisdom influenced, through Juan Carlos Scannone, the conceptualization and systematic development of the theology of the people. In this text I will refer firstly to the sapiential and symbolic in the thought of Rodolfo Kusch within the framework of the logic of negation and the sapientiality of the popular. (1) Second, I will present the absolute and founding wisdom in the context of native religions and popular thought. (2)